2015 International Conference on Unmanned Aircraft Systems (ICUAS) 2015
DOI: 10.1109/icuas.2015.7152361
|View full text |Cite
|
Sign up to set email alerts
|

A novel algorithm for distant aircraft detection

Abstract: In this paper a novel algorithm for distant aircraft detection for visual sense-and-avoid for UAV is presented. The algorithm uses local edge density to partition the frame into two types of regions. The first type is the unstructured or homogeneous part like sky region and the second part where there is a structured background, like high contrast clouds or terrain regions. The airplanes are detected on the two types of regions with different strategies. The algorithm was planned to run in an embedded environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
0
19
0
2
Order By: Relevance
“…where target looming information in the sky region is extracted from HMM filter outputs. As an alternative solution, Zarandy et al, recently suggested that the sensor aircraft could execute regular heading changes to improve observability of targets with minimal motion with respect to the ground clutter. Future work will investigate the suitability of our system for detecting aircraft with minimal motion relative to the background ground clutter.…”
Section: Discussion Lessons Learnt and Future Workmentioning
confidence: 99%
See 4 more Smart Citations
“…where target looming information in the sky region is extracted from HMM filter outputs. As an alternative solution, Zarandy et al, recently suggested that the sensor aircraft could execute regular heading changes to improve observability of targets with minimal motion with respect to the ground clutter. Future work will investigate the suitability of our system for detecting aircraft with minimal motion relative to the background ground clutter.…”
Section: Discussion Lessons Learnt and Future Workmentioning
confidence: 99%
“…Importantly, Zarandy et al . recently noted that true collision threats can appear stationary with respect to ground clutter [as illustrated in Fig.…”
Section: Background and Related Workmentioning
confidence: 99%
See 3 more Smart Citations